PENGARUH KEBIJAKAN MODAL KERJA AGRESIF TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAMA PERIODE 2009-2011 - ANTONO, DONNY PRASETYA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
This study aimed to examine the effect of working capital management policies within the company. By focusing the company's policy on the policy of aggressive working capital financing is measured by the variable Aggressive Financing Policy, Leverage, Size, Sales Growth, the company's profitability as measured by return on assets. While the company's profitability, measured by return on assets variable will be tested to see the impact the profitability of the firm as measured by the value of the variable Price Book Value. Using data from manufacturing companies in Indonesia Stock Exchange during the period 2009-2011 with a certain pre-determined criteria. The results of this study are aggressive policies selected by management and a significantly positive impact on the profitability of the company. This indicates that the more aggressive a company in the funding it will provide greater benefits. While the company's profitability is also significant and positive influence. This indicates that companies with large profit will increase the company's value in the eyes of the public and investors.